Anabolic Function Downstream of TOR Controls Trade-offs Between Longevity and Reproduction at the Level of Specific Tissues in C. elegans - Howard, Amber C.; Mir, Dilawar; Snow, Santina; Horrocks, Jordan; Sayed, Hussein; Ma, Zhengxin; Rogers, Aric N. (Frontiers in Aging, 2021)
As the most energetically expensive cellular process, translation must be finely tuned to environmental conditions. Dietary restriction attenuates signaling through the nutrient sensing mTOR pathway, which reduces translation and redirects resources to preserve the soma. These responses are associated with increased lifespan but also anabolic impairment, phenotypes also observed when translation is genetically suppressed. Here, we restricted translation downstream of mTOR separately in major tissues in C. elegans to better understand their roles in systemic adaptation and whether consequences to anabolic impairment were separable from positive effects on lifespan. Lowering translation in neurons, hypodermis, or germline tissue led to increased lifespan under well-fed conditions and improved survival upon withdrawal of food, indicating that these are key tissues coordinating enhanced survival when protein synthesis is reduced. Surprisingly, lowering translation in body muscle during development shortened lifespan while accelerating and increasing reproduction, a reversal of phenotypic trade-offs associated with systemic translation suppression. Suppressing mTORC1 selectively in body muscle also increased reproduction while slowing motility during development. In nature, this may be indicative of reduced energy expenditure related to foraging, acting as a “GO!” signal for reproduction. Together, results indicate that low translation in different tissues helps direct distinct systemic adaptations and suggest that unknown endocrine signals mediate these responses. Furthermore, mTOR or translation inhibitory therapeutics that target specific tissues may achieve desired interventions to aging without loss of whole-body anabolism.